Synthesis method and application of poly (N-heterocyclic carbene) copper material
By regulating the appearance and structure of the Kabin copper materials of the nitrogen high ring, the existing copper -based molecular catalytic materials have insufficient power catalytic performance under high current density, and the efficient hydrocarbon semi -hydrogenation reaction is achieved.
Patent Information
- Application Number
- CN202411451227.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing copper-based molecular catalytic materials are electrocatalyzed at low current density (<200mA/cm2), which is difficult to meet the requirements of alkyne semihydrogenation at high current density, and the polyazine heterocyclic carbene copper complexes are mostly not prepared. Regular morphology, electrocatalytic performance cannot meet the improved performance needs.
In the cooperation between the molecules of the pyramidine and the mimazole -based molecules, the growth rate of the growth rate is controlled to control the appearance of the polyimazole salt, and under the conditions of alkaline conditions Or spherical nitrogen -shaped nitrogen miscellaneous Copper Copper material.
The high -efficiency electrically catalytic semi -hydrogenation of alcohol to olefins is achieved at high current density (500mA/CM2), which improves the electrocatalytic performance of catalytic materials and meets increasingly improved performance needs.
Smart Images

Figure CN119331226A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of novel electrocatalytic materials, and in particular relates to a synthesis method of a polynitrogen heterocyclic carbene copper material and application thereof. Background Art
[0002] The efficient removal of alkyne impurities in olefin raw materials is a prerequisite for promoting the high-end development of downstream polyolefin products. Under the "dual carbon" strategy, the electrocatalytic alkyne semi-hydrogenation using clean and renewable electricity as the driving force and water as the hydrogen source at room temperature and pressure is a promising olefin impurity removal technology.
[0003] As the core part of the electrocatalytic semi-hydrogenation system, catalytic materials play a very important role in inhibiting side reactions and promoting the semi-hydrogenation of alkynes to alkenes. At present, electrocatalytic alkyne semi-hydrogenation materials are mainly copper-based catalytic materials, among which copper-based molecular catalytic materials have attracted widespread attention due to their clear structure and precise control of reaction pathways. However, molecular catalytic materials usually have low current density (<200mA / cm 2 Therefore, it is urgent to construct copper-based molecular catalytic materials for electrocatalytic half-hydrogenation of alkynes at high current density.
[0004] Polynitrogen heterocyclic carbene copper complexes have the advantages of strong electron donation properties, strong metal affinity and good conjugated stability of nitrogen heterocyclic carbene. They can firmly coordinate copper sites through metal-carbon bonds and are expected to be stable and efficient catalysis at high current density. However, most of the polynitrogen heterocyclic carbene copper complexes prepared so far have irregular morphologies, and the electrocatalytic performance of irregular polynitrogen heterocyclic carbene copper complexes as catalytic materials cannot meet the increasingly high performance requirements and still needs to be improved.
[0005] Based on this, the present invention provides a method for synthesizing a polynitrogen heterocyclic carbene copper material with controllable morphology and high electrocatalytic performance. Summary of the invention
[0006] The purpose of the present invention is to solve the problem that the polynitrogen heterocyclic carbene copper complexes prepared by the existing preparation methods are mostly irregular in morphology, and to provide a synthesis method of polynitrogen heterocyclic carbene copper materials and their applications. The method can controllably construct polynitrogen heterocyclic carbene copper materials and has universal applicability. The prepared polynitrogen heterocyclic carbene copper materials can achieve high current density (500mA / cm 2 ) Efficient electrocatalytic semihydrogenation of alkynes to alkenes.
[0007] To achieve the above purpose, the technical solution provided by the present invention is:
[0008] A method for synthesizing a polynitrogen heterocyclic carbene copper material is characterized in that it comprises the following steps:
[0009] 1) Using molecules with benzyl bromide groups as linkers, imidazole molecules as monomers, and acetonitrile or 1,4-dioxane as solvent I, the growth rates v in three different directions of x, y, and z are effectively regulated during the quaternization and self-assembly of the linkers and monomers by coordinating different types of linkers, monomers, and solvent I. x 、v y 、v z , the polyimidazole salt having a rod-like, flake-like or spherical shape can be prepared;
[0010] When v x >>v y =v z When v x ≥v y >>v z When v x =v y =v z When , a spherical polyimidazole salt is formed;
[0011] 2) under the protection of an inert atmosphere, using the polyimidazolate obtained in step 1) as a framework, deprotonating the imidazole salt and coordinating with a copper salt under alkaline conditions, and controllably constructing a rod-shaped, sheet-shaped or spherical polynitrogen heterocyclic carbene copper material;
[0012] The alkaline conditions are used here to perform deprotonation without affecting the skeleton structure, wherein the base used in the alkaline conditions is potassium carbonate, potassium tert-butoxide or 1,8-diazabicyclo[5.4.0]undec-7-ene.
[0013] Further, in step 1), when preparing the rod-shaped polyimidazole salt:
[0014] The linker is 2,4,6-tris(4-bromomethylphenyl)-1,3,5-triazine (TBPT), the monomer is 1,3,5-triimidazolylbenzene, the solvent I is acetonitrile, and the reaction temperature is 50-120°C;
[0015] When preparing flaky polyimidazole salts:
[0016] The linker is 2,4,6-tris(4-bromomethylphenyl)-1,3,5-triazine (TBPT), the monomer is di(1H-imidazol-1-yl)methane, the solvent I is 1,4-dioxane, and the reaction temperature is 50-120°C;
[0017] When preparing spherical polyimidazole salts:
[0018] The linker is 1,3,5-tris(4-bromomethylphenyl)benzene, the monomer is 1,3,5-triimidazolylbenzene or di(1H-imidazol-1-yl)methane, the solvent I is acetonitrile or 1,4-dioxane, and the reaction temperature is 50-120°C.
[0019] The reaction temperature is selected to be 50-120° C. If the temperature is too high, the reaction will be too fast and irregular products will be formed; if the temperature is too low, it will be unfavorable for the quaternization reaction.
[0020] Further, in step 1), the molar ratio of the linker to the monomer is 1:1 to 2:3;
[0021] The ratio of the raw material to the solvent I is 1:20-200, mmol / mL; the amount of the raw material here refers to the total amount of the linker and the monomer;
[0022] The reaction time is 15 to 48 hours.
[0023] Further, in step 2), the solvent II used is tetrahydrofuran, methanol or acetone;
[0024] The copper salt used is copper halide, cuprous halide or copper nitrate;
[0025] The copper salt, solvent II and base are used in a ratio of 9:50:5, mmol / mL / mmol;
[0026] The reaction temperature is 25-50°C;
[0027] The reaction time is 24 to 48 hours;
[0028] The inert atmosphere is nitrogen or argon.
[0029] The present invention also provides a polynitrogen heterocyclic carbene copper material with controllable morphology, which is prepared by the synthesis method and has a rod-like, sheet-like or spherical morphology.
[0030] In addition, the present invention also provides the use of the above-mentioned polynitrogen heterocyclic carbene copper material with controllable morphology as a catalytic material in the electrocatalytic preparation of olefins from alkynes.
[0031] Based on the above application, the present invention also provides a method for preparing olefins, which is special in that it comprises the following steps:
[0032] S1. The polynitrogen heterocyclic carbene copper material with controllable morphology obtained by the above-mentioned synthesis method is uniformly dispersed in solvent III as a catalytic material to obtain a catalytic material slurry;
[0033] S2. The catalytic material slurry obtained in S1 is evenly coated on the gas diffusion layer (the gas diffusion layer is placed on the flat plate material), and after being fully dried, it is used as a cathode for standby use;
[0034] S3. The cathode and anode obtained in S2 are matched to form an electrolytic cell, and the cathode electrolyte and the anode electrolyte are separated by an ion exchange membrane, and the alkyne raw material is subjected to an electrocatalytic alkyne semi-hydrogenation reaction to prepare olefins.
[0035] Further, in S1, the solvent III is water, ethanol, isopropanol, acetone, or a mixture of water and ethanol, isopropanol or acetone in any proportion;
[0036] The ratio of the catalytic material to the solvent III is 1-100:0.2-50, mg / mL.
[0037] Further, in S2, the gas diffusion layer is 5% polytetrafluoroethylene, which is placed on a flat plate material, and the material of the flat plate material is carbon fiber paper, carbon fiber woven cloth, non-woven fabric or carbon black paper;
[0038] The catalytic material slurry is evenly coated on the gas diffusion layer by spraying;
[0039] In S3, the anode is prepared by loading the anode material on the anode current collector by spraying, impregnation or electrodeposition; the anode material is a non-precious metal (Fe, Co, Ni, etc.) or its alloy or composite; the anode current collector is a copper current collector, a nickel current collector, a titanium current collector, carbon paper or carbon cloth; a nickel plate, a nickel sheet or a nickel foam can also be directly used as the anode, and the thickness of the nickel plate, the nickel sheet or the nickel foam is 0.05 to 1.0 mm;
[0040] The alkyne raw material is a gaseous alkyne raw material or a liquid alkyne raw material;
[0041] Wherein, the gaseous alkyne raw material is acetylene, propyne or butyne;
[0042] Liquid alkyne raw materials are liquid compounds containing carbon-carbon triple bonds.
[0043] Furthermore, in the S3 electrocatalytic process, the gaseous alkyne feedstock enters from the gas chamber inlet of the electrolytic cell, and the olefin is collected from the gas chamber outlet;
[0044] Alternatively, the liquid alkyne raw material and the cathode electrolyte are mixed and then enter the cathode chamber from the inlet, and the olefin is collected from the cathode chamber outlet; wherein the liquid alkyne raw material and the cathode electrolyte are mixed in a volume ratio of 1:1 to 1:199;
[0045] During electrocatalysis, the flow rate of the gaseous alkyne raw material is 1 to 100 sccm, the flow rate of the cathode electrolyte is 1 to 100 sccm, and the flow rate of the anode electrolyte is 1 to 100 sccm;
[0046] The flow rate of the liquid after the liquid alkyne raw material is mixed with the cathode electrolyte is 1 to 100 sccm, and the flow rate of the anode electrolyte is 1 to 100 sccm.
[0047] Furthermore, the cathode electrolyte and the anode electrolyte are acidic, neutral or alkaline liquid electrolytes, or solid electrolytes, such as: 0.01-5M hydrochloric acid, 0.01-5M sulfuric acid, 0.01-5M KCl solution, 0.01-10M KHCO3 solution or 0.01-10M KOH solution.
[0048] The advantages of the present invention are:
[0049] 1. The present invention realizes the controllable construction of rod-shaped, sheet-shaped and spherical polynitrogen heterocyclic carbene copper materials through a universal method; firstly, a molecule having a benzyl bromide group is used as a linker, an imidazole molecule is used as a monomer, and acetonitrile or 1,4-dioxane is used as a solvent. Through the coordination between different types of linkers, monomers and solvents, the controllable synthesis of rod-shaped, sheet-shaped and spherical polyimidazole salts is realized during the quaternization and self-assembly process of the linker and the monomer; then, under the protection of an inert atmosphere (argon or nitrogen), the polyimidazole salt synthesized in an alkaline environment is in situ deprotonated and coordinated with copper to prepare rod-shaped, sheet-shaped and spherical polynitrogen heterocyclic carbene copper. The material is a polymer with controllable morphology, which is significantly different from commercial carbene copper.
[0050] 2. The present invention further applies the controllably constructed polynitrogen heterocyclic copper carbene, using a gas diffusion electrode loaded with polynitrogen heterocyclic copper carbene catalytic material as a cathode, a non-precious metal-based catalytic material as an anode, and an ion exchange membrane (anion exchange membrane) or a proton exchange membrane as a separator between the cathode and the anode to assemble a gas diffusion electrolytic cell. The electrochemical performance test confirms that the polynitrogen heterocyclic copper carbene catalytic material of the present invention can achieve efficient electrocatalytic acetylene semi-hydrogenation, which is significantly better than other molecular-based catalytic materials. Compared with other molecular catalytic materials, the electrocatalytic current density (<200mA / cm 2 ), the polynitrogen heterocyclic carbene copper material prepared by the present invention can achieve high current density (500mA / cm 2 ) Efficient electrocatalytic semi-hydrogenation of alkynes to alkenes. More importantly, the polynitrogen heterocyclic carbene copper catalytic material developed in the present invention has a clear and simple structure, which is an important basis for further clarifying the active center and reaction mechanism of the polynitrogen heterocyclic carbene copper catalytic material in electrocatalysis. At the same time, it also provides a new idea for the wide application of polynitrogen heterocyclic carbene copper materials in electrocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 The present invention is a flow chart of a universal preparation method of the polynitrogen heterocyclic carbene copper material.
[0052] Figure 2 The synthetic route of rod-shaped IOP-NHC Cu is shown;
[0053] Figure 3 The synthetic route of rod-shaped PIS-1-NHC Cu is shown;
[0054] Figure 4 The synthetic route of sheet-like PIS-2-NHC Cu is shown in Figure 2.
[0055] Figure 5 The synthetic route of spherical POP-NHC Cu;
[0056] Figure 6 The scanning electron microscope images of rod-shaped, flake-shaped and spherical polynitrogen heterocyclic carbene copper materials are shown below; a is rod-shaped, b is flake-shaped, c is spherical, and d is irregular morphology;
[0057] Figure 7 It is a rod-shaped polyimidazole salt and a rod-shaped polynitrogen heterocyclic carbene copper 13 C solid NMR.
[0058] Figure 8 The polarization curve of rod-shaped polynitrogen heterocyclic carbene copper as cathode material and the Faraday efficiency distribution diagram under different current densities; where a is the polarization curve and b is the Faraday efficiency distribution diagram. DETAILED DESCRIPTION
[0059] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments:
[0060] The present invention provides a universal preparation method for polynitrogen heterocyclic carbene copper catalytic materials, such as Figure 1 As shown, the following steps are included:
[0061] 1) Using molecules with benzyl bromide groups as linkers, imidazole molecules as monomers, and acetonitrile or 1,4-dioxane as solvent I, the growth rates v in three different directions of x, y, and z are effectively regulated during the quaternization and self-assembly of the linkers and monomers by coordinating different types of linkers, monomers, and solvent I. x 、v y 、v z , the polyimidazole salt having a rod-like, flake-like or spherical shape can be prepared;
[0062] When v x >>v y =v z When v x ≥v y >>v z When v x =v y =v z When , a spherical polyimidazole salt is formed;
[0063] 2) Under the protection of an inert atmosphere, the polyimidazole salt obtained in step 1) is used as a skeleton, and the imidazole salt is deprotonated and coordinated with a copper salt under alkaline conditions to controllably construct a rod-shaped, sheet-shaped or spherical polyazacyclic carbene copper material; the base used in the alkaline conditions is potassium carbonate, potassium tert-butoxide or 1,8-diazabicyclo[5.4.0]undec-7-ene.
[0064] The following examples of this method construct polynitrogen heterocyclic carbene copper materials with controllable morphologies such as rods (IOP-NHC Cu, PIS-1-NHC Cu), sheets (PIS-2-NHCCu), and spheres (POP-NHC Cu); using a gas diffusion electrode loaded with polynitrogen heterocyclic carbene copper catalytic materials as the cathode, efficient electrocatalytic alkyne semi-hydrogenation at high current density is achieved.
[0065] The synthesis of the above-mentioned rod-shaped polynitrogen heterocyclic carbene copper (IOP-NHC Cu) is as follows Figure 2 As shown:
[0066] 0.0588 g of 2,4,6-tris(4-bromomethylphenyl)-1,3,5-triazine (TBPT), 2.0276 g of 1,3,5-triimidazolylbenzene (TImB) and 40 mL of acetonitrile (CH3CN) were added into a flask, the reaction temperature was controlled at 100 °C, the reaction was carried out for 24 h, the product was centrifuged three times with acetonitrile and vacuum dried to obtain white rod-shaped polyimidazole salt (IOP);
[0067] 20 mg of polyimidazole salt (IOP), 15 mg of copper chloride dihydrate (CuCl2·2H2O) and 5 mg of potassium tert-butoxide were weighed and added to 5 mL of anhydrous methanol in sequence. Under argon protection, the mixture was stirred at room temperature for 24 h. The obtained product was centrifuged three times with methanol and dried under vacuum to obtain rod-shaped IOP-NHC Cu.
[0068] The synthesis of the above-mentioned rod-shaped polynitrogen heterocyclic carbene copper (PIS-1-NHC Cu) is as follows Figure 3 As shown:
[0069] At 85°C, 2 mL of acetonitrile solution containing 0.0222 g of di(1H-imidazol-1-yl)methane (BIM) was added to 3 mL of acetonitrile solution containing 0.0588 g of 2,4,6-tris(4-bromomethylphenyl)-1,3,5-triazine (TBPT), and stirred for 15 h. The product was collected by centrifugation, and the obtained product was dried under vacuum to obtain a white linear (can be seen as a rod) polyimidazole salt (PIS-1);
[0070] Take 20 mg of PIS-1, 15 mg of copper chloride dihydrate (CuCl2·2H2O) and 5 mg of potassium tert-butoxide and add them to 5 mL of anhydrous methanol in sequence. Under argon protection, stir at room temperature for 24 h. The resulting product is centrifuged three times with methanol and dried under vacuum to obtain rod-shaped PIS-1-NHC Cu.
[0071] The synthesis of the above-mentioned sheet-like polynitrogen heterocyclic carbene copper (PIS-2-NHC Cu) is as follows Figure 4 As shown:
[0072] At 85°C, 2 mL of a 1,4-dioxane solution containing 0.0222 g of di(1H-imidazol-1-yl)methane (BIM) was added to 3 mL of a 1,4-dioxane solution containing 0.0588 g of 2,4,6-tris(4-bromomethylphenyl)-1,3,5-triazine (TBPT), and stirred for 24 h. The product was collected by centrifugation, and the obtained product was dried under vacuum to obtain a flaky white polyimidazole salt (PIS-2);
[0073] Take 20 mg of PIS-2, 15 mg of copper chloride dihydrate (CuCl2·2H2O) and 5 mg of potassium tert-butoxide and add them into 5 mL of anhydrous methanol in sequence. Under argon protection, stir at room temperature for 24 h. The obtained product is centrifuged three times with methanol and dried under vacuum to obtain flaky PIS-2-NHC Cu.
[0074] The synthesis of the spherical polynitrogen heterocyclic carbene copper (POP-NHC Cu) is as follows: Figure 5 As shown:
[0075] 0.0588 g of 1,3,5-tris(4-bromomethylphenyl)benzene (BbbT), 0.0276 g of 1,3,5-triimidazolylbenzene (TImB) and 40 mL of acetonitrile (CH3CN) were added to a flask. Under argon protection, the reaction temperature was controlled to 100 °C. The reaction was carried out for 24 h. The product was centrifuged three times with 15 mL of acetonitrile and vacuum dried to obtain a white spherical polyimidazole salt (POP).
[0076] Take 20 mg of POP, 15 mg of copper chloride dihydrate (CuCl2·2H2O) and 5 mg of potassium tert-butoxide and add them to 5 mL of anhydrous methanol in sequence. Under argon protection, stir at room temperature for 24 h. The resulting product is centrifuged three times with 15 mL of methanol and dried under vacuum to obtain spherical POP-NHC Cu.
[0077] like Figure 6 As shown, this method can obtain a rod-shaped, b sheet-shaped and c spherical polynitrogen heterocyclic carbene copper with controllable morphology.
[0078] like Figure 7As shown, compared with polyimidazole salt (IOP), polynitrogen heterocyclic carbene copper (IOP-NHC Cu) has a C 13 The solid-state NMR spectrum showed a characteristic peak of carbene carbon-copper bond at 184 ppm, indicating the successful synthesis of polynitrogen heterocyclic carbene copper.
[0079] In addition, the present invention also prepares the target product according to other matching modes among the linker, monomer and solvent I given above, and can obtain polynitrogen heterocyclic carbene copper materials of corresponding shapes.
[0080] Comparative Example:
[0081] 0.0588 g of 2,4,6-tris(4-bromomethylphenyl)-1,3,5-triazine (TBPT), 0.0276 g of 1,3,5-triimidazolylbenzene (TImB) and 20 mL of 1,4-dioxane were added to a flask. The reaction temperature was controlled to be 100 °C under argon protection. The reaction was carried out for 24 h. The product was centrifuged three times with 15 mL of 1,4-dioxane and vacuum dried to obtain an irregularly morphological polyimidazole salt (IOP-1).
[0082] 10 mg IOP-1, 5 mg copper chloride dihydrate (CuCl2·2H2O) and 3 mg potassium tert-butoxide were added to 5 mL anhydrous methanol in sequence. Under argon protection, the mixture was stirred at room temperature for 24 h. The obtained product was centrifuged three times with 15 mL methanol and dried under vacuum to obtain IOP-1-NHC Cu with irregular morphology, such as Figure 6 As shown in d.
[0083] It can be seen that the polynitrogen heterocyclic carbene copper catalytic material needs to be constructed in a controllable morphology according to the coordination method given above.
[0084] In order to verify the performance of the above products, the present invention conducted the following application tests on the catalytic materials according to the following process parameters:
[0085] Preparation of cathode electrode:
[0086] Accurately weigh a certain mass (1-100 mg) of the above-synthesized catalyst powder (rod-shaped, flake-shaped and spherical polynitrogen heterocyclic carbene copper materials), and disperse it in a certain volume (0.2-50 mL) of solvent (the solvent is water, ethanol, isopropanol, acetone or a mixture of water and ethanol, isopropanol or acetone in any proportion) to obtain a catalyst slurry;
[0087] A gas diffusion layer (5% polytetrafluoroethylene) was placed on a flat plate material, a certain volume (50-500 μL) of catalyst slurry was accurately measured and evenly sprayed on the gas diffusion layer. After sufficient drying, a gas diffusion electrode loaded with polynitrogen heterocyclic carbene copper was prepared as a cathode, with a catalyst loading of 0.1-10 mg / cm2 .
[0088] The above-mentioned flat plate material includes but is not limited to: carbon paper (such as carbon fiber paper), carbon cloth (carbon fiber woven cloth), non-woven fabric or carbon black paper, etc.
[0089] Preparation of anode electrode:
[0090] The anode is prepared by loading non-precious metals (Fe, Co, Ni, etc.) or their alloys and composites on the anode current collector by spraying, impregnation, electrodeposition, etc.; alternatively, a nickel plate, nickel sheet or nickel foam is directly used as the anode.
[0091] The anode current collector includes, but is not limited to, a copper current collector, a nickel current collector, a titanium current collector, carbon paper, carbon cloth, and the like.
[0092] Assembly of gas diffusion electrolytic cell and electrochemical performance testing:
[0093] Assembly of gas diffusion electrolysis cell:
[0094] The gas diffusion electrode loaded with polynitrogen heterocyclic carbene copper catalytic material prepared as above is used as cathode, matched with the above non-precious metal-based anode. The cathode electrolyte and the anode electrolyte are separated by an anion / cation exchange membrane, and the raw material can be gaseous alkyne raw material or liquid alkyne raw material. In the electrocatalytic alkyne semi-hydrogenation process, a gaseous alkyne raw material enters from a gas chamber inlet of an electrolytic cell, and olefins (i.e., alkyne semi-hydrogenation products) are collected from a gas chamber outlet, wherein the flow rate of the gaseous alkyne raw material is 1 to 100 sccm, the flow rate of the cathode electrolyte is 1 to 100 sccm, and the flow rate of the anode electrolyte is 1 to 100 sccm; a liquid alkyne raw material and a cathode electrolyte are mixed and enter from a cathode chamber inlet, and olefins (i.e., alkyne semi-hydrogenation products) are collected from a cathode chamber outlet, wherein the liquid alkyne raw material and the cathode electrolyte are mixed in a volume ratio of 1:1 to 1:199, the flow rate of the mixed liquid is 1 to 100 sccm, and the flow rate of the anode electrolyte is 1 to 100 sccm.
[0095] The gaseous alkyne raw material is acetylene, propyne or butyne, or a gas mixture of the foregoing gases and other substances (gaseous olefins, inert gases, etc.);
[0096] The liquid alkyne raw material is a liquid compound containing a carbon-carbon triple bond, or a liquid mixture thereof with other substances (liquid olefins, etc.).
[0097] The cathode electrolyte and the anode electrolyte are acidic, neutral, alkaline liquid electrolytes or solid electrolytes, such as: 0.01-5M hydrochloric acid, 0.01-5M sulfuric acid, 0.01-5M KCl solution, 0.01-10M KHCO3 solution or 0.01-10M KOH solution.
[0098] The electrochemical performance of the electrocatalytic alkyne semi-hydrogenation reaction was tested using an electrochemical workstation. The reaction activity of the catalyst was tested using cyclic scanning voltammetry and linear scanning voltammetry, and the selectivity and stability of the semi-hydrogenation product of the catalytic material was tested using constant potential or constant current combined with gas chromatography.
[0099] Next, appropriate catalytic materials are selected in combination with specific alkyne compounds, and the electrocatalytic alkyne semi-hydrogenation performance (activity, Faraday efficiency and other performance indicators) of the catalytic materials are tested.
[0100] [Example 1]
[0101] (1) Carbon paper sprayed with a certain mass of rod-shaped polynitrogen heterocyclic carbene copper (IOP-NHC Cu) is used as the cathode of the electrolytic cell; commercial nickel foam is used as the anode of the electrolytic cell; the cathode electrolyte and the anode electrolyte are both 1M KOH solution, and the cathode and the anode are separated by an anion exchange membrane.
[0102] (2) The flow rate of the reaction gas is controlled to be 30 sccm by a gas mass flow meter. The composition of the acetylene compound raw material used in the experiment is: acetylene.
[0103] (3) The flow rates of the cathode electrolyte and the anode electrolyte were controlled at 4 sccm using a peristaltic pump.
[0104] (4) Cyclic voltammetry and linear sweep voltammetry were used to test the electrocatalytic acetylene semi-hydrogenation performance of the catalytic material at 500 mA / cm 2 Under electric current, the types and contents of gas products were analyzed by online gas chromatography, and their Faraday efficiency was calculated.
[0105] [Example 2]
[0106] (1) Carbon paper sprayed with a certain mass of rod-shaped polynitrogen heterocyclic carbene copper (IOP-NHC Cu) is used as the cathode of the electrolytic cell; commercial nickel foam is used as the anode of the electrolytic cell; the cathode electrolyte and the anode electrolyte are both 1M KOH solution, and the cathode and the anode are separated by an anion exchange membrane.
[0107] (2) The flow rate of the reaction gas is controlled to be 30 sccm by a gas mass flow meter. The composition of the acetylene compound raw material used in the experiment is: acetylene.
[0108] (3) The flow rates of the cathode electrolyte and the anode electrolyte were controlled at 4 sccm using a peristaltic pump.
[0109] (4) Cyclic voltammetry and linear sweep voltammetry were used to test the electrocatalytic acetylene semi-hydrogenation performance of the catalytic material at 300 mA / cm 2 Under electric current, the types and contents of gas products were analyzed by online gas chromatography, and their Faraday efficiency was calculated.
[0110] [Example 3]
[0111] (1) Carbon paper sprayed with a certain mass of rod-shaped polynitrogen heterocyclic carbene copper (PIS-1-NHC Cu) is used as the cathode of the electrolytic cell; commercial nickel foam is used as the anode of the electrolytic cell; the cathode electrolyte and the anode electrolyte are both 1M KOH solution, and the cathode and the anode are separated by an anion exchange membrane.
[0112] (2) The flow rate of the reaction gas is controlled to be 30 sccm by a gas mass flow meter. The composition of the acetylene compound raw material used in the experiment is: acetylene.
[0113] (3) The flow rates of the cathode electrolyte and the anode electrolyte were controlled at 4 sccm using a peristaltic pump.
[0114] (4) Cyclic voltammetry and linear sweep voltammetry were used to test the electrocatalytic acetylene semi-hydrogenation performance of the catalytic material at 500 mA / cm 2 Under electric current, the types and contents of gas products were analyzed by online gas chromatography, and their Faraday efficiency was calculated.
[0115] [Example 4]
[0116] (1) Carbon paper sprayed with a certain mass of rod-shaped polynitrogen heterocyclic carbene copper (PIS-1-NHC Cu) is used as the cathode of the electrolytic cell; commercial nickel foam is used as the anode of the electrolytic cell; the cathode electrolyte and the anode electrolyte are both 1M KOH solution, and the cathode and the anode are separated by an anion exchange membrane.
[0117] (2) The flow rate of the reaction gas is controlled to be 30 sccm by a gas mass flow meter. The composition of the acetylene compound raw material used in the experiment is: acetylene.
[0118] (3) The flow rates of the cathode electrolyte and the anode electrolyte were controlled at 4 sccm using a peristaltic pump.
[0119] (4) Cyclic voltammetry and linear sweep voltammetry were used to test the electrocatalytic acetylene semi-hydrogenation performance of the catalytic material at 300 mA / cm 2 Under electric current, the types and contents of gas products were analyzed by online gas chromatography, and their Faraday efficiency was calculated.
[0120] [Example 5]
[0121] (1) A carbon paper sprayed with a certain mass of flaky polynitrogen heterocyclic carbene copper (PIS-2-NHC Cu) is used as the cathode of the electrolytic cell; a commercial nickel foam is used as the anode of the electrolytic cell; the cathode electrolyte and the anode electrolyte are both 1M KOH solutions, and the cathode and the anode are separated by an anion exchange membrane.
[0122] (2) The flow rate of the reaction gas is controlled to be 30 sccm by a gas mass flow meter. The composition of the acetylene compound raw material used in the experiment is: acetylene.
[0123] (3) The flow rates of the cathode electrolyte and the anode electrolyte were controlled at 4 sccm using a peristaltic pump.
[0124] (4) Cyclic voltammetry and linear sweep voltammetry were used to test the electrocatalytic acetylene semi-hydrogenation performance of the catalytic material at 500 mA / cm 2 Under electric current, the types and contents of gas products were analyzed by online gas chromatography, and their Faraday efficiency was calculated.
[0125] [Example 6]
[0126] (1) A carbon paper sprayed with a certain mass of flaky polynitrogen heterocyclic carbene copper (PIS-2-NHC Cu) is used as the cathode of the electrolytic cell; a commercial nickel foam is used as the anode of the electrolytic cell; the cathode electrolyte and the anode electrolyte are both 1M KOH solutions, and the cathode and the anode are separated by an anion exchange membrane.
[0127] (2) The flow rate of the reaction gas is controlled to be 30 sccm by a gas mass flow meter. The composition of the acetylene compound raw material used in the experiment is: acetylene.
[0128] (3) The flow rates of the cathode electrolyte and the anode electrolyte were controlled at 4 sccm using a peristaltic pump.
[0129] (4) Cyclic voltammetry and linear sweep voltammetry were used to test the electrocatalytic acetylene semi-hydrogenation performance of the catalytic material at 300 mA / cm 2 Under electric current, the types and contents of gas products were analyzed by online gas chromatography, and their Faraday efficiency was calculated.
[0130] [Example 7]
[0131] (1) A carbon paper sprayed with a certain mass of spherical polynitrogen heterocyclic carbene copper (POP-NHC Cu) is used as the cathode of the electrolytic cell; a commercial nickel foam is used as the anode of the electrolytic cell; the cathode electrolyte and the anode electrolyte are both 1M KOH solutions, and the cathode and the anode are separated by an anion exchange membrane.
[0132] (2) The flow rate of the reaction gas is controlled to be 30 sccm by a gas mass flow meter. The composition of the acetylene compound raw material used in the experiment is: acetylene.
[0133] (3) The flow rates of the cathode electrolyte and the anode electrolyte were controlled at 4 sccm using a peristaltic pump.
[0134] (4) Cyclic voltammetry and linear sweep voltammetry were used to test the electrocatalytic acetylene semi-hydrogenation performance of the catalytic material at 500 mA / cm 2Under electric current, the types and contents of gas products were analyzed by online gas chromatography, and their Faraday efficiency was calculated.
[0135] [Example 8]
[0136] (1) A carbon paper sprayed with a certain mass of spherical polynitrogen heterocyclic carbene copper (POP-NHC Cu) is used as the cathode of the electrolytic cell; a commercial nickel foam is used as the anode of the electrolytic cell; the cathode electrolyte and the anode electrolyte are both 1M KOH solutions, and the cathode and the anode are separated by an anion exchange membrane.
[0137] (2) The flow rate of the reaction gas is controlled to be 30 sccm by a gas mass flow meter. The composition of the acetylene compound raw material used in the experiment is: acetylene.
[0138] (3) The flow rates of the cathode electrolyte and the anode electrolyte were controlled at 4 sccm using a peristaltic pump.
[0139] (4) Cyclic voltammetry and linear sweep voltammetry were used to test the electrocatalytic acetylene semi-hydrogenation performance of the catalytic material at 300 mA / cm 2 Under electric current, the types and contents of gas products were analyzed by online gas chromatography, and their Faraday efficiency was calculated.
[0140] [Example 9]
[0141] (1) A carbon paper sprayed with a certain mass of spherical polynitrogen heterocyclic carbene copper (TOP-NHC Cu) is used as the cathode of the electrolytic cell; a commercial nickel foam is used as the anode of the electrolytic cell; the cathode electrolyte and the anode electrolyte are both 1M KOH solutions, and the cathode and the anode are separated by an anion exchange membrane.
[0142] (2) The flow rate of the reaction gas is controlled to be 30 sccm by a gas mass flow meter. The composition of the acetylene compound raw material used in the experiment is: acetylene.
[0143] (3) The flow rates of the cathode electrolyte and the anode electrolyte were controlled at 4 sccm using a peristaltic pump.
[0144] (4) Cyclic voltammetry and linear sweep voltammetry were used to test the electrocatalytic acetylene semi-hydrogenation performance of the catalytic material at 500 mA / cm 2 Under electric current, the types and contents of gas products were analyzed by online gas chromatography, and their Faraday efficiency was calculated.
[0145] [Example 10]
[0146] (1) A carbon paper sprayed with a certain mass of spherical polynitrogen heterocyclic carbene copper (TOP-NHC Cu) is used as the cathode of the electrolytic cell; a commercial nickel foam is used as the anode of the electrolytic cell; the cathode electrolyte and the anode electrolyte are both 1M KOH solutions, and the cathode and the anode are separated by an anion exchange membrane.
[0147] (2) The flow rate of the reaction gas is controlled to be 30 sccm by a gas mass flow meter. The composition of the acetylene compound raw material used in the experiment is: acetylene.
[0148] (3) The flow rates of the cathode electrolyte and the anode electrolyte were controlled at 4 sccm using a peristaltic pump.
[0149] (4) Cyclic voltammetry and linear sweep voltammetry were used to test the electrocatalytic acetylene semi-hydrogenation performance of the catalytic material at 300 mA / cm 2 Under electric current, the types and contents of gas products were analyzed by online gas chromatography, and their Faraday efficiency was calculated.
[0150] [Comparative Example 1]
[0151] (1) 0.0588 g of 2,4,6-tris(4-bromomethylphenyl)-1,3,5-triazine (TBPT), 0.0276 g of 1,3,5-triimidazolylbenzene (TImB) and 20 mL of 1,4-dioxane were added to a flask, the reaction temperature was controlled to 100 °C under argon protection, the reaction was carried out for 24 h, the product was centrifuged three times with 1,4-dioxane and vacuum dried to obtain an irregular morphology of polyimidazole salt (IOP-1);
[0152] 10 mg of the above-mentioned irregular morphology IOP-1, 10 mg of copper chloride dihydrate (CuCl2·2H2O) and 3 mg of potassium tert-butoxide were weighed and added into 5 mL of anhydrous methanol in sequence. Under argon protection, the mixture was stirred at room temperature for 24 h. The obtained product was centrifuged three times with methanol and dried under vacuum to obtain irregular morphology IOP-1-NHC Cu.
[0153] (2) Carbon paper sprayed with a certain mass of IOP-1-NHC Cu was used as the cathode of the electrolytic cell; commercial nickel foam was used as the anode of the electrolytic cell; the cathode electrolyte and the anode electrolyte were both 1M KOH solutions, and the cathode and anode were separated by an anion exchange membrane.
[0154] (3) The flow rate of the reaction gas is controlled to be 30 sccm by a gas mass flow meter. The composition of the acetylene compound raw material used in the experiment is: acetylene.
[0155] (4) The flow rates of the cathode electrolyte and the anode electrolyte were controlled at 4 sccm using a peristaltic pump.
[0156] (5) Cyclic voltammetry and linear sweep voltammetry were used to test the electrocatalytic acetylene semi-hydrogenation performance of the catalytic material at 500 mA / cm 2 Under electric current, the types and contents of gas products were analyzed by online gas chromatography, and their Faraday efficiency was calculated.
[0157] [Comparative Example 2]
[0158] (1) A carbon paper sprayed with a certain mass of rod-shaped polyimidazole salt (IOP) is used as the cathode of the electrolytic cell; a commercial nickel foam is used as the anode of the electrolytic cell; the cathode electrolyte and the anode electrolyte are both 1M KOH solutions, and the cathode and the anode are separated by an anion exchange membrane.
[0159] (2) The flow rate of the reaction gas is controlled to be 30 sccm by a gas mass flow meter. The composition of the acetylene compound raw material used in the experiment is: acetylene.
[0160] (3) The flow rates of the cathode electrolyte and the anode electrolyte were controlled at 4 sccm using a peristaltic pump.
[0161] (4) Cyclic voltammetry and linear sweep voltammetry were used to test the electrocatalytic acetylene semi-hydrogenation performance of the catalytic material at 500 mA / cm 2 Under electric current, the types and contents of gas products were analyzed by online gas chromatography, and their Faraday efficiency was calculated.
[0162] [Comparative Example 3]
[0163] (1) Weigh 20 mg of rod-shaped polyimidazole salt (IOP) and 15 mg of copper chloride dihydrate (CuCl2·2H2O) and add them into 5 mL of anhydrous methanol in sequence. Under argon protection, stir at room temperature for 24 h. The obtained product is centrifuged three times with methanol and vacuum dried to obtain rod-shaped polyimidazole salt copper (IOP-Cu).
[0164] (2) Carbon paper sprayed with a certain mass of IOP-Cu is used as the cathode of the electrolytic cell; commercial nickel foam is used as the anode of the electrolytic cell; the cathode electrolyte and the anode electrolyte are both 1M KOH solutions, and the cathode and the anode are separated by an anion exchange membrane.
[0165] (3) The flow rate of the reaction gas is controlled to be 30 sccm by a gas mass flow meter. The composition of the acetylene compound raw material used in the experiment is: acetylene.
[0166] (4) The flow rates of the cathode electrolyte and the anode electrolyte were controlled at 4 sccm using a peristaltic pump.
[0167] (5) Cyclic voltammetry and linear sweep voltammetry were used to test the electrocatalytic acetylene semi-hydrogenation performance of the catalytic material at 500 mA / cm 2 Under electric current, the types and contents of gas products were analyzed by online gas chromatography, and their Faraday efficiency was calculated.
[0168] The specific evaluation results are shown in Table 1 below.
[0169] Table 1
[0170]
[0171]
[0172]
[0173] As shown in Table 1, the electrocatalytic performance of the polynitrogen heterocyclic carbene copper material obtained by the present invention and the molecular-based catalytic material were compared. Under the same test conditions, when 500 mA / cm 2 At the current density, the ethylene Faraday efficiency of polynitrogen heterocyclic carbene copper materials (rod-shaped IOP-NHC Cu: 96%; flake-shaped PIS-2-NHC Cu: 91.4%; spherical TOP-NHC-Cu: 92%) is generally higher than that of other molecular-based catalytic materials (irregular morphology IOP-1-NHC Cu: 69%; IOP-Cu: 76%). Figure 8 As shown, the rod-shaped polynitrogen heterocyclic copper carbene has a current density of 100-500 mA / cm 2 The ethylene Faraday efficiency can reach more than 95% within the current density range, among which, when the current density is 300mA / cm 2 The Faraday efficiency of ethylene can reach 99%. At the same time, the current density used for electrocatalysis of polynitrogen heterocyclic carbene copper materials is significantly higher than the value reported in existing literature. In addition, under the same current density, the applied potential of polynitrogen heterocyclic carbene copper materials is generally lower than that of other molecular-based catalytic materials, which saves energy while ensuring the yield of ethylene. The polynitrogen heterocyclic carbene copper material developed by the present invention has a clear structure, which lays a good foundation for studying the electrocatalytic active center and reaction mechanism, and also provides a new idea for the application of polynitrogen heterocyclic carbene copper materials in the field of electrocatalysis.
[0174] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should be included in the protection scope of the present invention.
Claims
1. A method for synthesizing a polynitrogen heterocyclic carbene copper material, characterized in that: The following steps are involved: 1) Using molecules with benzyl bromide groups as linkers, imidazole molecules as monomers, and acetonitrile or 1,4-dioxane as solvent I, the growth rates v in three different directions of x, y, and z are effectively regulated during the quaternization and self-assembly of the linkers and monomers by coordinating different types of linkers, monomers, and solvent I. x 、v y 、v z , the polyimidazole salt having a rod-like, flake-like or spherical shape can be prepared; When v x >>v y =v z When v x ≥v y >>v z When v x =v y =v z When , a spherical polyimidazole salt is formed; 2) under the protection of an inert atmosphere, using the polyimidazolate obtained in step 1) as a framework, deprotonating the imidazolate and coordinating with a copper salt under alkaline conditions, and controllably constructing a rod-shaped, sheet-shaped or spherical polynitrogen heterocyclic carbene copper material; The base used in the alkaline condition is potassium carbonate, potassium tert-butoxide or 1,8-diazabicyclo[5.4.0]undec-7-ene.
2. The synthesis method according to claim 1, characterized in that: In step 1), when preparing a rod-shaped polyimidazole salt: The linker is 2,4,6-tris(4-bromomethylphenyl)-1,3,5-triazine (TBPT), the monomer is 1,3,5-triimidazolylbenzene, the solvent I is acetonitrile, and the reaction temperature is 50-120°C; When preparing flaky polyimidazole salts: The linker is 2,4,6-tris(4-bromomethylphenyl)-1,3,5-triazine (TBPT), the monomer is di(1H-imidazol-1-yl)methane, the solvent I is 1,4-dioxane, and the reaction temperature is 50-120°C; When preparing spherical polyimidazole salts: The linker is 1,3,5-tris(4-bromomethylphenyl)benzene, the monomer is 1,3,5-triimidazolylbenzene or di(1H-imidazol-1-yl)methane, the solvent I is acetonitrile or 1,4-dioxane, and the reaction temperature is 50-120°C.
3. The synthesis method according to claim 2, characterized in that: Step 1), the molar ratio of the linker to the monomer is 1:1 to 2:3; The ratio of the raw material to the solvent I is 1:20-200, mmol / mL; the amount of the raw material here refers to the total amount of the linker and the monomer; The reaction time is 15 to 48 hours; In step 2), the solvent II used is tetrahydrofuran, methanol or acetone; The copper salt used is copper halide, cuprous halide or copper nitrate; The copper salt, solvent II and base are used in a ratio of 9:50:5, mmol / mL / mmol; The reaction temperature is 25-50°C; The reaction time is 24 to 48 hours; The inert atmosphere is nitrogen or argon.
4. A polynitrogen heterocyclic carbene copper material with controllable morphology, characterized in that: The product is prepared by the synthesis method according to any one of claims 1 to 3, and has a rod-like, sheet-like or spherical morphology.
5. Use of the polynitrogen heterocyclic carbene copper material with controllable morphology as claimed in claim 4 as a catalytic material in the electrocatalytic preparation of olefins from alkynes.
6. A method for preparing olefins, characterized in that: The following steps are involved: S1. The polynitrogen heterocyclic carbene copper material with controllable morphology obtained by the synthesis method of any one of claims 1 to 3 is uniformly dispersed in solvent III as a catalytic material to obtain a catalytic material slurry; S2. The catalytic material slurry obtained in S1 is evenly coated on the gas diffusion layer and fully dried as a cathode; S3. The cathode and anode obtained in S2 are matched to form an electrolytic cell, and the cathode electrolyte and the anode electrolyte are separated by an ion exchange membrane or a proton exchange membrane, and the alkyne raw material is subjected to an electrocatalytic alkyne semi-hydrogenation reaction to prepare olefins.
7. The preparation method according to claim 6, characterized in that: In S1, the solvent III is water, ethanol, isopropanol, acetone, or a mixture of water and ethanol, isopropanol or acetone in any proportion; The ratio of the catalytic material to the solvent III is 1-100:0.2-50, mg / mL.
8. The preparation method according to claim 6 or 7, characterized in that: In S2, the gas diffusion layer is 5% polytetrafluoroethylene, which is placed on a flat plate material, and the material of the flat plate material is carbon fiber paper, carbon fiber woven cloth, non-woven fabric or carbon black paper; The catalytic material slurry is evenly coated on the gas diffusion layer by spraying; In S3, the anode is prepared by loading the anode material on the anode current collector by spraying, impregnation or electrodeposition; the anode material is a non-precious metal or its alloy or composite; the anode current collector is a copper current collector, a nickel current collector, a titanium current collector, carbon paper or carbon cloth; The alkyne raw material is a gaseous alkyne raw material or a liquid alkyne raw material; Wherein, the gaseous alkyne raw material is acetylene, propyne or butyne; Liquid alkyne raw materials are liquid compounds containing carbon-carbon triple bonds.
9. The preparation method according to claim 8, characterized in that: In the S3 electrocatalytic process, the gaseous alkyne feedstock enters from the gas chamber inlet of the electrolytic cell, and the olefin is collected from the gas chamber outlet; Alternatively, the liquid alkyne raw material and the cathode electrolyte are mixed and then enter the cathode chamber from the inlet, and the olefin is collected from the cathode chamber outlet; wherein the liquid alkyne raw material and the cathode electrolyte are mixed in a volume ratio of 1:1 to 1:199; During electrocatalysis, the flow rate of the gaseous alkyne raw material is 1 to 100 sccm, the flow rate of the cathode electrolyte is 1 to 100 sccm, and the flow rate of the anode electrolyte is 1 to 100 sccm.
10. The preparation method according to claim 9, characterized in that: The cathode electrolyte and the anode electrolyte are 0.01-5M hydrochloric acid, 0.01-5M sulfuric acid, 0.01-5M KCl solution, 0.01-10M KHCO3 solution or 0.01-10M KOH solution.
Citation Information
Patent Citations
Nitrogen-impurity carbene-class palladium catalyst and preparation method and application thereof
CN103418438A
Synthesis method of copper-nitrogen heterocyclic carbene complex catalyst
CN111100147A